Clinical Pharmacology Of Antimalarial Drugs. - Navaratnam, Profesor Madya (Dr.) V. (Pusat Penyelidikan Dadah dan Ubat-Ubatan Universiti Sains Malaysia, 1989)
Under the joint sponsorship of the Universiti Sains Malaysia, Penang, and the UNDP/WHO/World Bank Special Programme for Research and Training in Tropical Diseases, a Workshop on the clinical pharmacology of antimalarial drugs was held in Penang on 23 January - 4 February 1989. This Workshop brought together scientists from a wide variety of disciplines and nationalities who had in common the interest and experience in the clinical pharmacology of antimalarial drugs.